Evidence produced by qualitative investigations on type 2 diabetes: a review of the literature - Marcelo Eduardo Pfeiffer Castellanos; Nelson Filice de Barros; Cristiane Spadacio; Sarah Monte Alegre; Philip Tovey; Alex Broom
Type 2 diabetes has a major impact on patients lives and the healthcare network. Given the growth in qualitative information on diabetes, it becomes important to systematize this knowledge. A meta-study on diabetes was conducted through analysis on 42 articles that were made in journals at the periodicals portal of the Coordination Office for Advancement of Higher-level Personnel (Capes). We found that the studies reviewed had a good theoretical basis, which included: care management, health-disease concepts, professional-patient relationships, professional practices and treatment compliance. The articles clearly described the methodological procedures used. The use of interviews and focal groups for data gathering predominated, and it was sought to explore different views of the individuals investigated. It was reaffirmed that it was important for health professionals and managers to implement healthcare policies, programs and models that are appropriate for the specific features of chronic illness, guided by comprehensive care and co-responsibility.